1995
DOI: 10.1146/annurev.py.33.090195.001003
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Plant Disease Severity and Yield

Abstract: The relationship between disease and yield is most often summarized as a simple empirical model that describes average crop performances is the presence of a pathogen. Such models may be robust and useful for surveys but their use is usually constrained to the specific conditions under which the modal was developed. Changes in production system usually invalidate the relationship. The alternative is to base the relationship on an epidemiological analysis of the pathogen population and a physiological concept o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0
8

Year Published

1997
1997
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(64 citation statements)
references
References 29 publications
1
55
0
8
Order By: Relevance
“…As revealed by O'Brien and Van Bruggen [36], the inaccuracies made while measuring disease in the field are a major constraint, when relating disease to yield, and in some cases, there may be no relationship between these two variables. Similar studies by Waggoner and Berger [37], Gaunt [34] and Filho et al [38] have indicated that the measurement of disease severity, based on lesion number or leaf area, may be less related to yield.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…As revealed by O'Brien and Van Bruggen [36], the inaccuracies made while measuring disease in the field are a major constraint, when relating disease to yield, and in some cases, there may be no relationship between these two variables. Similar studies by Waggoner and Berger [37], Gaunt [34] and Filho et al [38] have indicated that the measurement of disease severity, based on lesion number or leaf area, may be less related to yield.…”
Section: Discussionsupporting
confidence: 63%
“…The inconsistency in results could be explained by the Gaunt [34] theory, which states that the green leaf area and the green area duration is directly correlated to yield, in both the healthy and diseased crop species. The observations from the study show that Season B, which had higher disease infection, also had better climatic conditions, resulting in longer green leaf area duration, which culminated in higher yields.…”
Section: Discussionmentioning
confidence: 99%
“…Decrease in disease severity caused simultaneous increase in bulb weight. Gaunt (1995) explains reduction in yield because of low radiation interceptions and radiation use efficiency caused by foliar diseases. …”
Section: Yield Parametersmentioning
confidence: 99%
“…The term tolerance has been used widely and inconsistently in the literature and for a number of years this hindered the development of a clear conceptual framework for research into the physiological mechanisms underlying tolerance (Gaunt, 1981;Clarke, 1984). Some authors have used the term tolerance to describe partial or incomplete resistance to infection.…”
Section: 1mentioning
confidence: 99%
“…More commonly, tolerance has been defi ned in terms of the ability to maintain an acceptable seed yield, or some other measure of plant fi tness or productivity, under a given severity of pathogen infection, thus distinguishing it from resistance (Caldwell et al, 1958;Schafer, 1971). A further distinction has been made between tolerance of the pathogen and tolerance of disease (Gaunt, 1981;Clarke, 1984;Newton et al, 1998;Inglese & Paul, 2006). According to Inglese & Paul (2006) tolerance of infection is the relationship between the presence of the pathogen and disruption of normal host physiology, whereas tolerance of disease is the relationship between host growth or fi tness and the physiological disruption resulting from infection.…”
Section: 1mentioning
confidence: 99%